Mapping the recruitment pathways of core spindle assembly checkpoint proteins - Mallal, Daniel, author; DeLuca, Jennifer, advisor; Markus, Steven, advisor; Spencer, John, committee member (Colorado State University. Libraries, 2017)
The Spindle Assembly Checkpoint (SAC) is a vital regulatory pathway in eukaryotic cells to ensure proper division of duplicated chromosomes such that each daughter cell receives a complete and equal copy of genetic material. The SAC specifically ensures that kinetochores form proper attachments to spindle microtubules by preventing anaphase until every chromosome is bi-oriented and attached at each pair of kinetochores to microtubules emanating from opposite spindle poles. The SAC is a highly regulated and intricate network of proteins which allows for a robust inhibitory signal to be produced in the presence of erroneous attachments, halting cells in anaphase allowing for error correction. An important set of interactions occurs surrounding the proteins Bub1, BubR1, BuGZ binding to Bub3 mediated through a GLEBS domain binding Bub3. The precise nature of the interplay between these proteins binding to Bub3 is rather unclear and requires further characterization. Here we set out to characterize the direct recruitment sufficiency of each of these proteins. In order to distinguish the direct recruitment sufficiency of each individual protein, we targeted Bub1, BubR1, Bub3, and BuGZ individually to an ectopic site on chromosomes away from the kinetochore. We find that Bub1, BubR1, and Bub3 are sufficient to recruit each other as well as BuGZ, however BuGZ is only able to recruit Bub3 indicating that the Bub3-BuGZ GLEBS interaction is the strongest of the three. Interestingly, we also find that BuGZ is able to recruit Bub3 less efficiently in mitotic cells, suggesting a regulatory mechanism that decreases the affinity of BuGZ for Bub3 as cells transition into mitosis. Together, these data support a model in which BuGZ is exchanged for Bub1 to bind Bub3 at kinetochores in mitosis to promote efficient SAC signaling.
Keywords: Bub3; BuGZ; Bub1; spindle assembly checkpoint; BubR1